A Pyrazolate‐Bridged Bis(pentadentate) Ligand and Its Dinuclear Ruthenium Complex. Issue 26 (September 2015) - Sander, Anett C.; Schober, Anne; Dechert, Sebastian; Meyer, Franc
Abstract: A new bis(pentadentate) pyrazole‐bridged proligand HL bis5 providing two N5 binding pockets and its diruthenium complex [L bis5 Ru2 (MeCN)2 ](PF6 )3 (1 ) have been synthesized, and the structure of1 has been elucidated by X‐ray diffraction. The two exogenous MeCN ligands in1 are both directed into the central pocket created by the two metal ion compartments and interfere with each other, which leads to some distortion of the dimetallic framework. According to an Eyring analysis of variable‐temperature NMR spectroscopic data, interconversion of the resulting enantiomeric forms is rapid with a free activation energy of Δ G ≠ = 43.7 kJ mol –1 at 298 K (Δ H ≠ = 30.8 kJ mol –1, Δ S ≠ = –43.2 J mol –1 K –1 ). Cyclic voltammetry of1 shows two sequential reversible oxidations at ca. 0.85 and 1.25 V (vs. SCE), and the mixed‐valent Ru III Ru II species has been characterized by spectroelectrochemistry, UV/Vis/NIR and EPR spectroscopy. Complex1 was found to be a poor catalyst for water oxidation: under standard conditions [triflic acid, pH 1, using cerium(IV) ammonium nitrate as oxidant] rapid degradation by oxidative ligand fragmentation at its benzylic‐type CH2 groups was observed. Abstract : A new pyrazolate‐bridged ligand has been developed that can bind two metal ions in two pentadentate compartments, leaving a single site per metal atom for binding of exogenous substrates within the dimetallic pocket. A dinuclear Ru complex illustrates the structural features, dynamics, and electronic coupling induced by the new ligand framework.